Rheopheresis for Digital Ulcers and Raynaud's Phenomenon in Systemic Sclerosis Refractory to Conventional Treatments - Korsten, Peter; Müller, Gerhard A.; Rademacher, Jan-Gerd; Zeisberg, Michael; Tampe, Björn (Frontiers in Medicine, 2019)
Raynaud's phenomenon (RP) is almost universally present in patients with Systemic Sclerosis (SSc). RP represents a generalized vasculopathy and potentially lead to digital ulcers (DU), which may be complicated by superinfection, tissue necrosis, and limb loss. We report the analysis of an extracorporeal procedure in a 36-year-old female patient with diffuse SSc with refractory RP and DU despite treatment with diltiazem, candesartan, sildenafil, and intravenous iloprost. We performed rheopheresis (RheoP), a variant of double-filtration plasmapheresis, as a potential new treatment option for refractory patients despite optimal medical therapy. We performed two RheoP per week every 4 weeks for a total of 3 months. Clinical improvement in DU healing occurred with no adverse events directly related to the treatment. While there was no reduction in the number of Raynaud attacks with RheoP, a significant reduction of the duration of attacks from a median of 15 (5–45, 95% CI 10–15) to 7 (3–30, 95% CI 6–10) minutes with an improvement of the Raynaud Condition Score (RCS) improved from 4 to 2. In conclusion, RheoP is a feasible and potentially beneficial treatment modality in patients with refractory RP and DU. We propose that RheoP should be investigated in a larger number of patients in a clinical trial setting.